Digital Leapfrogging And Balanced Integration: SocioPhilosophical Trajectories Of Uzbekistan’s Digital Transformation (Zien Journal of Social Sciences and Humanities, 2026)
This study evaluates the socio-philosophical and structural dynamics of Uzbekistan’s integration into the global information society during the Fourth Industrial Revolution. Moving beyond technocentric paradigms, the analysis employs a multidimensional framework incorporating technological, institutional, human, and cultural-spiritual vectors. The article evaluates the transition from an infrastructuralfoundational phase (1991–2016) to a strategic acceleration phase (2017–present), contrasting rapid technological expansion with the slower development of human and institutional competencies. By examining digital architecture through institutional economics and social philosophy, this paper analyzes the structural dualisms of modern platform models and identifies future scenarios for sustainable, humancentric development in Central Asia